Sign "O" the times [compact disc] - Prince (Paisley Park : Distributed by Warner Bros., 1987)
Personnel: Prince (vocals, various instruments); Lisa Coleman (vocals, sitar, wooden flute, keyboards); Sheila E. (vocals, percussion); Susannah, Jill Jones, Sheena Eastson, Camille (vocals); Wendy Melvoin (guitar, percussion, background vo.